2017
DOI: 10.3389/fnbot.2017.00069
|View full text |Cite
|
Sign up to set email alerts
|

Golden Gait: An Optimization Theory Perspective on Human and Humanoid Walking

Abstract: Human walking is a complex task which includes hundreds of muscles, bones and joints working together to deliver harmonic movements with the need of finding equilibrium between moving forward and maintaining stability. Many different computational approaches have been used to explain human walking mechanisms, from pendular model to fractal approaches. A new perspective can be gained from using the principles developed in the field of Optimization theory and in particularly the branch of Game Theory. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
(76 reference statements)
2
18
0
Order By: Relevance
“…The gait phases, and in particular the ratio between stance and swing phases, have been highlighted as fundamental for a harmonic walking because they formed, together with the double support phases, a fractal autosimilar structure of walking ( 19 ). The autosimilarity of the ratios between consecutive gait phases is altered in pathological conditions ( 20 , 21 ), but in physiological conditions, walking allows for an optimization of energy expenditure ( 21 ) and an optimal equilibrium between balance and speed ( 22 ). In our study, the FSLR showed that a longer stance phase was associated to the identification of patients (OR = 1.547).…”
Section: Discussionmentioning
confidence: 99%
“…The gait phases, and in particular the ratio between stance and swing phases, have been highlighted as fundamental for a harmonic walking because they formed, together with the double support phases, a fractal autosimilar structure of walking ( 19 ). The autosimilarity of the ratios between consecutive gait phases is altered in pathological conditions ( 20 , 21 ), but in physiological conditions, walking allows for an optimization of energy expenditure ( 21 ) and an optimal equilibrium between balance and speed ( 22 ). In our study, the FSLR showed that a longer stance phase was associated to the identification of patients (OR = 1.547).…”
Section: Discussionmentioning
confidence: 99%
“…In this case all the spatiotemporal parameters were described as a percentage of the gait cycle, modelled as an inverted pendulum [ 20 , 21 , 39 , 40 ]. This inverted pendulum model [ 20 , 21 , 39 , 40 ] can be written in the form of an equation which describes the swinging movement of the legs according to: where SL 1 is the step length (m), L is the length of the leg (m) expressed as “the summit between the iliac crest and the floor” [ 41 ] and h is the amplitude of the center of mass (COM) oscillation during a walking pattern [ 20 , 21 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…They can also be used for analyzing what we call the golden gait approximation, relating the inverted pendulum model to a fractal approach of walking, where an approximation of 1.61 ratio is seen between spatio-temporal parameters such as stance and swing of gait cycle [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The golden ratio, "phi" indeed is present in nature, math, physics, and sometimes deliberately used in design [13][14][15][16]. Iosa et al [8][9][10] restated this as a well-known expression of consecutive Fibonacci terms:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation